2022
DOI: 10.1002/cctc.202201107
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dual Vacancies in TiO2 for Enhanced Photocatalytic Hydrogen Generation and Pollutants Removal

Abstract: The mechanism of TiO2 with Ti vacancy and O vacancy in photocatalytic hydrogen production is unknown. Herein, TiO2 with three types of vacancies was constructed. It was found that DV‐Ti‐3O containing both O vacancies and Ti vacancies had the highest photocatalytic hydrogen production of 12.42 mmol ⋅ g−1 ⋅ h−1 twice that of SV‐Ti, where the O vacancy acted as an emitter providing a directional path for the migration of photogenerated electrons and provided the adsorption sites for water molecules, while the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…As a result, anionic-cationic dual vacancies may occur in pairs in single semiconductors. [43][44][45][46] The crystal mode of anionic-cationic dual-vacancy within single crystals is shown in Scheme 2c; the previously reported cases include Bi 2 WO 6 with negatively charged tungsten vacancy (V W ) and positively charged oxygen vacancy (V O ), 47 TiO 2 with negatively charged Ti and positively charged O dual vacancies, 48 and Bi 3 O 4 Br with negatively charged Bi and positively charged O dual vacancies, as shown in Fig. 1c.…”
Section: Dual-vacancy Schemesmentioning
confidence: 99%
“…As a result, anionic-cationic dual vacancies may occur in pairs in single semiconductors. [43][44][45][46] The crystal mode of anionic-cationic dual-vacancy within single crystals is shown in Scheme 2c; the previously reported cases include Bi 2 WO 6 with negatively charged tungsten vacancy (V W ) and positively charged oxygen vacancy (V O ), 47 TiO 2 with negatively charged Ti and positively charged O dual vacancies, 48 and Bi 3 O 4 Br with negatively charged Bi and positively charged O dual vacancies, as shown in Fig. 1c.…”
Section: Dual-vacancy Schemesmentioning
confidence: 99%
“…[6][7][8][9] To achieve a satisfactory overall water splitting efficiency, the photocatalyst should not only have appropriate conduction and valence band positions, but the light-generated carriers should also have a long enough lifetime to participate in the interfacial reactions. [10][11][12][13] The Z-scheme or S-scheme heterojunction photocatalysts based on a composite of two semiconductor materials have emerged as a key research area for photocatalytic water splitting, and several artificial heterojunction photocatalysts with impressive solar to chemical efficiencies have been developed. [14][15][16][17][18] For example, Maeda et al reported a new BaZrO 3 -BaTaO 2 N solid solution coupled with rutile-type titanium dioxide forming Z-scheme heterojunction photocatalysts with visible light absorption up to 660 nm can achieve solar energy conversion efficiencies of 0.014 % for producing hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…However, photocatalytic overall water splitting is extremely difficult because it is not only a thermodynamically difficult uphill reaction to overcome the Gibbs free energy of 237 kJ/mol, but also it involves a four‐electron/hole multi‐step [6–9] . To achieve a satisfactory overall water splitting efficiency, the photocatalyst should not only have appropriate conduction and valence band positions, but the light‐generated carriers should also have a long enough lifetime to participate in the interfacial reactions [10–13] . The Z‐scheme or S‐scheme heterojunction photocatalysts based on a composite of two semiconductor materials have emerged as a key research area for photocatalytic water splitting, and several artificial heterojunction photocatalysts with impressive solar to chemical efficiencies have been developed [14–18] .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, seeking renewable clean energy to replace traditional fossil fuels is a significant but challenging issue. Photocatalytic H 2 evolution from water is an alternative, renewable, environmentally friendly, and economically practical technology to utilize solar energy, but the key point is to develop photocatalysts with high activity and stability. The main factors affecting the H 2 evolution activity of photocatalysts include excellent optical absorption ability and greater stability along with high separation and migration efficiency of photogenerated holes and electrons. , As everyone knows, sunlight has a wide range of wavelengths, with high-energy ultraviolet light accounting for only 4% and visible light accounting for more than 40%. , Consequently, recently, more and more attention has been paid to develop visible-light-responsive photocatalysts. , Polypyridyl ruthenium complexes are the most widely used photoredox catalysts because of their excellent photochemical properties. First, their maximum absorption wavelength is in the visible region, indicating that they are easily excited by visible light.…”
Section: Introductionmentioning
confidence: 99%